Efectiveness of PBL Model Assisted By 3D Animation Media On Motivation and Learning Outcomes of Science in Elementary School - Ifah Larasati; Tri Astuti (Universitas Negeri Malang, 2025)
Abstract: Problem Based Learning focuses students in an active and collaborative. This study aims to; 1) analyze the effectiveness of the PBL model assisted by 3D animation media on science learning motivation; 2) analyze the effectiveness of the PBL model assisted by 3D animation media on science learning outcomes; 3) testing the effectiveness of the PBL model assisted by 3D animation media on science learning motivation and outcomes. The research used in this study is Quantitative Experiment (True Experimental Design) with Posttest-Only Control Design research. The results of the study found that 1) the PBL model assisted by 3D animation media is effective for learning motivation, with a significance value of 0.014 < 0.05 meaning that H0 is not accepted so H1 is accepted. 2) the PBL model assisted by 3D animation media is effective for learning motivation. 3) The PBL model assisted by 3D animation media is effective for motivation and learning outcomes, with a significance value of X to Y1 of 4.503 and X to Y2 of 5.483 more than t table = 1.711. Overall, this research is very feasible to optimize the motivation and learning outcomes of science. Abstrak: Pembelajaran Berbasis Masalah (Problem Based Learning/PBL) menekankan keterlibatan aktif dan kolaboratif siswa dalam proses belajar. Penelitian ini bertujuan untuk: (1) menganalisis efektivitas model PBL berbantuan media animasi 3D terhadap motivasi belajar IPA; (2) menganalisis efektivitas model PBL berbantuan media animasi 3D terhadap hasil belajar IPA; dan (3) menguji efektivitas model PBL berbantuan media animasi 3D terhadap motivasi dan hasil belajar IPA secara simultan. Metode penelitian yang digunakan adalah eksperimen kuantitatif dengan desain True Experimental Design menggunakan Posttest-Only Control Design. Hasil penelitian menunjukkan bahwa: (1) model PBL berbantuan media animasi 3D efektif meningkatkan motivasi belajar IPA, dengan nilai signifikansi 0,014 < 0,05, yang berarti H₀ ditolak dan H₁ diterima; (2) model PBL berbantuan media animasi 3D juga efektif dalam meningkatkan hasil belajar IPA; dan (3) model tersebut terbukti efektif secara simultan terhadap motivasi dan hasil belajar, ditunjukkan oleh nilai signifikansi dari X ke Y₁ sebesar 4,503 dan X ke Y₂ sebesar 5,483, lebih besar dari t tabel = 1,711. Dengan demikian, model PBL berbantuan animasi 3D layak diterapkan untuk mengoptimalkan motivasi dan hasil belajar IPA siswa.